Poetic Audio Description: The State of the Art in Canada - Bergonzoni, Carolina (Journal of Audiovisual Translation, 2025)
This article explores the development of poetic Audio Description (AD) in live dance performances, with a focus on the Canadian context. Poetic AD embraces metaphor, sensory language, and embodied descriptions, enhancing accessibility while expanding the artistic potential of AD. Through a reflection on past experiences and the recent Languaging Dance project, this paper examines creative and collective approaches to live AD that emphasize embodied, sensory, and poetic language. By integrating improvisational and artistic techniques, poetic AD emerges as both an inclusive and aesthetic form of engagement with dance. This research contributes to broader discussions on inclusive arts practices, accessibility aesthetics, and multisensory engagement in live dance AD. Lay summary This study looks at how poetic language can make Audio Descriptions (AD) more meaningful for Blind and Low Vision (BLV) audiences during live dance performances. The AD approach presented goes beyond simply adding accessibility after the show is done; it helps make dance performances richer and more inclusive for everyone involved from the start. As such, the article suggests that involving BLV artists in creating AD can improve the descriptions. The article looks at the Canadian context and using reflections from Languaging Dance, a research project that took place in 2023-2024, it shows that poetic AD can bring dance to life through vivid, poetic language, making it a more engaging experience.